Knowledge of Fertile Period and Its Determinants Among Women of Childbearing age in Ethiopia: A Multilevel Analysis Based on 2016 Ethiopian Demographic and Health Survey - Maereg Wolde; Ayenew Kassie; Kegnie Shitu; Zelalem Nigussie Azene (Frontiers in Public Health, 2022)
BackgroundThe knowledge of the fertile period is one of the science techniques used to delay pregnancy. Although it is a highly effective method, most women lack correct knowledge about it and end up with unintended pregnancies and undergo through unsafe abortion, which is among the leading factors for maternal death. Therefore, this study is aimed to assess the knowledge about fertile period and its determinant factors among reproductive age women in Ethiopia.MethodsThe data were extracted from the 2016 national cross-sectional Ethiopian Demographic and Health Survey. The data were collected using a two-stage cluster design. Descriptive statistics were used to summarize the study findings. The determinants of knowledge about fertile period were analyzed using a multilevel binary logistic regression model.ResultsA total of 15,683 women were included. From this, 23.6% (95% CI: 23–24) had knowledge about fertile period. Age group of 20–24 years, 25–29 years, 30–34 years, 35–39 years, 40–44 years, and 45–49 years; accomplishment of primary education, secondary education, and higher education; partner high level of education; wealth status of poorer, middle, richer, and richest; a person listened to radio < once a week; and a person who watch TV at least once in a week and who ever heard about family planning; internet usage in the last 12 months, being protestant religion follower; and community family planning message exposure were significantly associated with knowledge about fertile period.ConclusionThe number of reproductive age women who know about fertile period is low in Ethiopia. Age above 19 years, respondent's education attainment from primary to higher education, partner high level of education, being from poorer to richest wealth status, listening to radio, watching TV, ever heard of FP, internet usage in the last 12 months, being protestant religion follower, and community family planning exposure were significantly associated with good knowledge about fertile period.